Investigation of Compressive Behavior of Pre-folded Thin-walled Column Fabricated by 3D Printing - Farid Triawan; Elin Rachmawati; Bentang Arief Budiman; Djati Wibowo Djamari; Andy Saputro; Ilman Arpi (Indonesian Journal of Science and Technology, 2021)
This paper reveals the mechanical behavior of thin-walled columns with pre-folded patterns subjected to compressive loading. The column specimens (Polylactic Acid) are fabricated using Fused Deposition Modeling 3D printer and subjected to quasi-static compressive loading to investigate their mechanical behavior (by modifying the specimens' cross-section patterns and folding angles). The column specimens are simulated by finite element analysis to understand how the stress distribution and local deformation affecting the stiffness, strength, and overall deformation. The experiments showed that introducing the pre-folded pattern in a thin-walled column with different cross-sections can dramatically lower its structural stiffness (85%) and compressive strength (69%), but increase its deformability (115%), which is good agreement with numerical simulation. The variation of cross-section patterns and pre-folding angle could effectively modify the compressive mechanical behavior. Moreover, the results demonstrate how the FDM 3D Printing method can be used in fabricating a thin-walled column with irregular shapes and then to modify its deformability. This finding can be useful for designing any complex structures requiring specific stiffness and deformation such as suspension devices, prosthetic devices in biomechanics, and robotic structures.